A highly fire-safe and smoke-suppressive single-component epoxy resin with switchable curing temperature and rapid curing rate. (15th February 2021) - Yang, Shuang; Huo, Siqi; Wang, Jun; Zhang, Bin; Wang, Jingsheng; Ran, Shiya; Fang, Zhengping; Song, Pingan; Wang, Hao
Abstract: The design of highly fire-safe and smoke-suppressive single-component epoxy (EP) resins combining modest curing temperature and fast curing rate has been desirable yet very challenging in both academia and industry. Herein, we report a facile design of a phosphorus/imidazole-containing single-component EP system via incorporating 9, 10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) and a flame-retardant curing agent cyclotriphosphazene-modified benzimidazole (BICP) into EP. Our results show that EP/DOPO/BICP exhibits a rapid modest-temperature curing feature because DOPO serves as a switch that triggers BICP to release benzimidazole (BIM) via substitution reaction in the initial curing stage. Moreover, as-prepared EP/DOPO/BICP shows outstanding fire retardancy, reflected by the high limited oxygen index (LOI) of 38.3% and UL-94 V-0 rating. Compared to the control EP system, the peak of heat release rate (PHRR) and total smoke production (TSP) of EP/DOPO/BICP remarkably decrease by 74.5% and 50.6%, respectively, which is superior to previously-reported flame-retardant P-containing epoxy counterparts. The significant enhancements in flame retardancy and smoke suppression are mainly due to the formation of a highly intumescent char layer and the reduced burning degree of pyrolysis fragments. This work offers a facile and scalable strategy for creating fast-curing, modest-temperature curable, highly fire-resistant and smoke-suppressive one-component epoxy systems applicable to large-scale industrial production. Graphical abstract: Image 1